The effects of golden sea cucumber extract (Stichopus hermanii) on the number of lymphocytes during the healing process of traumatic ulcer on wistar rat’s oral mucous - Ira Arundina; Yuliati Yuliati; Pratiwi Soesilawati; Dian W Damaiyanti; Dania Maharani (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2015)
Background: Indonesia is a country with the world’s biggest potential and producer of sea cucumbers. Golden sea cucumber contains glicosaminoglycans, such as heparan sulphate and chondroitin sulphate, which could have a positive implication on wound healing process. This acceleration of wound healing process could be observed through the increasing of lymphocytes on ulcus traumaticus. Purpose: This study aims to analyze the effects of golden sea cucumber extract on the number of lymphocytes during the healing process of traumatic ulcer on Wistar rat’s oral mucous. Method: Golden sea cucumber extrat was made with freeze-dried method, and then gel was prepared using PEG 400 and PEG 4000 solvent. Twenty male rats with mucosal ulcus made were divided into a control group and three treatment groups with 20%, 40% and 80% golden sea cucumber extracts. All samples were euthanized on day 4 and then a preparation for histopathological examination was made to examine the number of lymphocytes. Result: The biggest number of lymphocytes was found in the treatment group with 40% golden sea cucumber extract, while the lowest one was found in the control group. The results of one way Anova test then showed a significant difference between the control group and the treatment groups. And, the results of Tukey HSD showed a significant difference between the control group and the treatment group with 40% golden sea cucumber extract. Conclusion: It can be concluded that 40% golden sea cucumber (Stichopus hermanii) extract can increase the number of lymphocytes during the healing process of traumatic ulcer on Wistar rat’s oral mucous.